Theoretical and Experimental Investigations of Braking Energy Recovery in Automobiles and Heavy Machinery - J. Ocioszyński (Engineering Transactions, 2005)
The paper deals with theoretical computations and experiments concerning the possibility of energy recuperation in certain phases of automobile and heavy machinery driving cycles as well as in working cycles of heavy machinery working mechanisms.